Capture, transport, and husbandry of elephant sharks (Callorhinchus milii) adults, eggs, and hatchlings for research and display - Boisvert, Catherine; Martins, C.; Edmunds, A.; Cocks, J.; Currie, P. (2014)
Elephant sharks (Callorhinchus milii) have the slowest evolving genome of all vertebrates and are an interesting model species for evolution research and a prized display animal. However, their deep water habitat, short breeding season, fragility, and susceptibility to stress-induced mortality have made them difficult animals to capture, keep in captivity, and obtain fertilized eggs from. Gravid females were captured by rod and reel from Western Port Bay, Australia and transferred to a 40000L closed aquaculture system to lay their eggs before being released. The water quality parameters, averaged over three seasons of 4-6 weeks (mean ± standard deviation) were: 16.8°C ± 2.31, salinity 37.1 ± 2.9g/L, ammonia 0.137 ± 0.2mg/L, nitrite levels 0.89 ± 0.9mg/L, nitrate 66.8 ± 45.6mg/L, pH 7.8 ± 0.18, dissolved oxygen levels 93.6 ± 5.3%, ORP 307 ± 63.3mV. Eggs were incubated in purpose built egg cages and embryos hatched after 143.6 days ± 1.3 at 16.9 ± 0.9°C of incubation. These procedures led to no adult mortality in the last 2 years and 620 eggs with known deposition date were collected over 4 years, of which 81.5% (±4.8) were viable. Collection of abundant embryological material with known deposition date is of paramount importance for evolutionary developmental research. We attribute this success to excellent water quality, maximum reduction of stress during capture, transport, handling, and captive care.